A modified approach for the synthesis of biologically relevant 5-substituted-2-N-aryl-1, 3-oxazole derivatives in mild conditions. Issue 1 (1st January 2020) - Udhayasurian, R.; Sivakumar, K.; Sajith, Ayyiliath M.; Joy, Muthipeedika Nibin
Abstract : We herein report a modified approach for the synthesis of some pharmacologically relevant oxazole derivatives linked with amides under mild conditions. The utilization of polymer-supported triphenylphosphine (poly-TPP) as a phosphine ligand for generating the key iminophosphorane intermediate was found to be vital for achieving the synthesis of oxazole in room temperature. This alternative approach relying on the cyclization reaction of readily available phenacyl azide and phenyl isothiocyanate rendered the oxazole derivative 3a in excellent yield. This methodology has been applied for the synthesis of a more decorated oxazole derivative 3b having ester functionality and was further converted to different amides under microwave irradiation in good to excellent yields in the later stage. GRAPHICAL ABSTRACT: UF0001